Desenvolvimento de um programa em python, para análise de vigas pelo método das seções - Oliveira, Webert Araújo (Universidade Federal Rural do Semi-Árido, 2018)
In this paper, important concepts will be presented on materials resistance, such as bending, beam designs and others. Such topics are critical to structural engineering. Thus, several important issues will be addressed in this area, such as: the basic elements, the influential forces in the structures and the methodologies created to evolve this branch of engineering. The objective of this work was the development of a program with the programming language python, whose function is to present to the user the resolution of structural problems for the analysis of beams, using the method of the sections. As a result, the program will report on all the steps, equations, resolutions and graphs used by the methodology discussed for beam analysis. Finally, some considerations were made about the advantages offered by the program, as well as some suggestions for its improvement, as well as the analysis of exercises proposed by books to check plot diagrams for internal efforts.
Monografia
Keywords: Engenharia estrutural; Python; Método das seções; Vigas; Relatório; ENGENHARIAS::ENGENHARIA CIVIL